IMPROVING READING COMPREHENSION OF THE EIGHTH-GRADE STUDENTS OF SMPN 3 SUKAWATI IN ACADEMIC YEAR 2022/2023 THROUGH KWL STRATEGY - Komang Ayu Amaravati Kamiana Putri; Anak Agung Putri Maharani; I Nengah Astawa (Academic Journal on English Studies (AJOES), 2023)
Reading is the activity involved in acquiring information and comprehending it from written sources. According to study done by researchers, the majority of VIII G students at SMPN 3 Sukawati in academic year 2022/2023 also experience quite serious problems in reading skills, they still have difficulty identifying for general information, the specific information, textual meaning, and textual references. Researchers are interested in whether the Know Want Learn (KWL) strategy may help eighth-grade pupils at SMPN 3 Sukawati enhance their reading comprehension. To accomplish these objectives, researchers conduct classroom activities. Two cycles of class actions were conducted to gather information via tests and questionnaires. Researchers need to compare the two data to find a substantial improvement in the subject's average score from pre-test to post-test. A questionnaire that included supporting information from the class action was the last test, the findings of which indicated that KWL deployment had been successful. Thus, it can be inferred from the findings of classroom action study that KWL can enhance the reading comprehension of eighth-grade students at SMPN 3 Sukawati for the academic year 2022–2023.